Bioengineered microneedles and nanomedicine as therapeutic platform for tissue regeneration - Yi-an Mao; Shihui Xu; Xiaozhou Shi; Yanjia Jin; Zihan Pan; Tian Hao; Guoping Li; Xuerui Chen; Hongdong Wang; Yongtao Wang; Junjie Xiao (Journal of Nanobiotechnology)
Abstract Tissue regeneration remains one of the most formidable challenges in modern medicine, particularly in the treatment of chronic wounds, organ damage, and degenerative diseases. These conditions are characterized by dysregulated healing, irreversible cell loss, and disrupted microenvironments that are resistant to conventional therapy. Traditional approaches, such as surgical grafts and systemic drug delivery, often fall short due to the limitations in specificity, efficacy, and safety. Emerging technologies, especially microneedles (MNs), nanomedicine, and their integration offer an innovative solution by enabling localized, controlled, and minimally invasive interventions. This review explores the challenges and therapeutic strategies associated with MNs and nanomedicine in tissue regeneration and cancer-related treatment. It highlights recent design innovations, functional diversity of bioengineered MNs, and the transformative potential of combining MNs with nanomedicine for precision regenerative therapies in specific tissues. The future perspectives of MNs and nanomedicine suggest promising avenues for smart and personalized regeneration. Graphical Abstract